INTRODUCTION TO INTEGRATED AGRICULTURAL SYSTEMS IN ELEMENTARY SCHOOL AGE CHILDREN IN CIVILIZATION SCHOOLS - Musfiroh Musfiroh; Suryani Gultom (Sean Institute, 2022)
The aim of the activity is to provide basic knowledge and skills on how to use land with an integrated farming system by combining the cultivation of kale, catfish and rabbit farming in one agricultural area. The introduced integrated farming system is expected to be implemented on a small scale in schools by utilizing the limited land area in schools. The target for introducing this integrated farming system is students from grades 1 to grade 6 at the Serang Civilization School, Serang District, Serang District. The material provided includes the understanding of integrated farming systems, their benefits and the types of commodities that can be used in integrated agriculture and the procedures for implementing them. This service activity succeeded in transferring basic knowledge and skills in growing vegetables and raising fish and rabbits. From this activity it can be concluded that the students know what is meant by integrated farming and its benefits. This activity is also supported by the school because it is integrated with subject matter and there is optimal use of school land.